Computers in Cardiology, 2005 2005
DOI: 10.1109/cic.2005.1588040
|View full text |Cite
|
Sign up to set email alerts
|

Increased dispersion of ventricular repolarization during recovery from exercise

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This may be different for the ventricular gradient. In a previous study we have demonstrated, in exercise ECGs, that the ventricular gradient during the exercise phase differs from the ventricular gradient during the recovery phase, when measured at equal heart rates [18]. This is due to the differences in circulating catecholamines and sympathetic and parasympathetic tone measured in these different physiological situations, similar differences may also occur during routine ECG recordings when patients are not given ample time to accommodate to a complete resting state.…”
Section: Independent Variablementioning
confidence: 82%
“…This may be different for the ventricular gradient. In a previous study we have demonstrated, in exercise ECGs, that the ventricular gradient during the exercise phase differs from the ventricular gradient during the recovery phase, when measured at equal heart rates [18]. This is due to the differences in circulating catecholamines and sympathetic and parasympathetic tone measured in these different physiological situations, similar differences may also occur during routine ECG recordings when patients are not given ample time to accommodate to a complete resting state.…”
Section: Independent Variablementioning
confidence: 82%
“…Franz et al [ 22 ] showed that the transient from a steady-state APD at a given stimulation cycle length (CL) towards a new steady-state APD after a step change in stimulation CL takes several minutes, or several hundreds of beats. More dynamic CL changes (e.g., a gradual decrease followed by a gradual increase) that are too fast for steady-state APD adaptation can cause hysteresis in the APD–CL relationship [ 23 , 24 ] and, consequently, in the ECG (e.g., during the exercise and recovery phase of an exercise test [ 25 ]).…”
Section: Introductionmentioning
confidence: 99%